KRITERIA VITALITAS BAHASA TALONDO - Buha Aritonang (Badan Pengembangan dan Pembinaan Bahasa, 2016)
This research was conducted in the village of Talondo Kondo, District Bonehau, Mamuju, West Sulawesi province with the aim to determine the vitality of the Talondo languages criteria.The methods of the research was done by doing the field research and the literature study.A fieldwork was conducted to obtain primary data while the library research obtaining secondary data. The sources of data in this study were 81 respondents from Talondo language native speakers. The datas are obtained from observations and questionnaires.To determine the vitality of Talondo language criteria the research used Likert scale models to test and compare the mean index of vitality. The calculation result of subindex groups with respondent characteristics (based on gender, age group, education level, and occupation) showed that the vitality of a Talondo language was setbacks. Because the average value addition and division of the total index of the four variables with the variables gender, age group, education level, and type of work is 0.58. The range value of its included in the index line 3—4 based on visualization in a spider diagram. ABSTRAKPenelitian ini dilaksanakan di Desa Talondo Kondo, Kecamatan Bonehau, Kabupaten Mamuju, Provinsi Sulawesi Barat dengan tujuan untuk menentukan kriteria vitalitas bahasa Talondo. Metode pengumpulan data dilakukan dengan penelitian lapangan dan pustidaka. Penelitian lapangan dilakukan untuk memperoleh data primer, sedangkan penelitian pustidaka untuk memperoleh data sekunder. Sumber data dalam penelitian ini adalah 81 responden penutur bahasa Talondo. Data diperoleh dari hasil pengamatan dan kuesioner. Untuk menentukan kriteria vitalitas bahasa Talondo digunakan model skala Likert dan indeks dengan uji compare mean. Hasil perhitungan kelompok subindeks dengan karakteristik responden (jenis kelamin, kelompok usia, jenjang pendidikan, dan jenis pekerjaan) menunjukkan bahwa vitalitas bahasa Talondo masuk kriteria mengalami kemunduran. Hal itu disebabkan karena nilai penjumlahan dan pembagian rerata indeks total keempat variabel dengan variabel jenis kelamin, kelompok usia, jenjang pendidikan, dan jenis pekerjaan adalah 0,58. Nilai 0,58 termasuk pada garis indeks 3—4 berdasarkan visualisasinya pada diagram laba-laba.